Does Knowing the Word Matter for Preschool DLLS? Individualized Vocabulary Words on Phonological Awareness Performance - Kathleen A. Paciga; Christina M. Cassano (SAGE Publishing, 2024)
Early literacy assessment has become commonplace in the preschool years, with phonological awareness constituting one component of emergent literacy targeted by such practices. This within-subjects experimental study examines the role of word familiarity on 93 dual language preschoolers' performance on phoneme-level awareness tasks in three-phoneme words. A researcher-designed digital tool created individualized test items (foils and target responses) for each child. Half of the items presented target responses that contained familiar words, and half contained unfamiliar words. Results suggest unknown/unfamiliar target words yield lower phonological awareness performance scores.